Linking lake debris pollution, tourist acceptance, and sustainability management in a freshwater tourism destination: evidence from Lake Koto Kampar, Indonesia - Iswahyudi Iswahyudi; R.A. Dodi Sukma; Zhulvie Meylanzharie; Zakiyatuz Zhulva Nabila Wahyudi; Muhammad Ilman Wahyudi; Marchel Putra Garfansa; Yenni Arista Cipta Ekalaturrahmah; Siti Alfiatul Amani; Sugiono Sugiono (Total Environment Advances, 2026)

Optimising site selection for ecosystem approaches to shrimp aquaculture in mangrove systems - Dominic Muenzel; Aji W. Anggoro; Dewi Embong Bulan; Yadi; Nurfadilah; Rahadian Pratama; Muhammad Ilman; Basir; Mariski Nirwan; Vabian Adriano; Muhammad M. Bayyan; Topik Hidayat; et al. (Aquaculture International, 2025)
Indonesia has experienced significant mangrove loss due to aquaculture expansion, particularly for shrimp farming, leading to the degradation of habitats and critical ecosystem services such as carbon storage, coastal protection, and fish spawning grounds. Ecosystem based aquaculture approaches offer a pathway to both mitigate environmental impacts and support sustainable seafood production. Here we explore the implementation of the Shrimp-Carbon Aquaculture (SECURE) approach in Berau Regency, East Kalimantan, Indonesia, which integrates mangrove restoration with organic shrimp farming to achieve sustainable aquaculture. Using environmental DNA (eDNA) metabarcoding to detect species from DNA shed into the environment, we assessed impacts of SECURE intervention compared to traditional ponds and found increased abundance of key taxonomic groups associated with healthy aquatic ecosystems, such as phytoplankton Chaetoceros, Chlorophyceae, and Cryptomonadales and zooplankton Calanoida and Cyclopoida. We then conducted a spatial prioritisation analysis to identify additional areas for SECURE implementation, considering mangrove restoration and protection potential, profitability, and intervention costs. High-priority ponds for restoration were typically set back from riverbanks, large, and spatially clustered, indicating opportunities for cost-effective, strategic expansion. This study underscores how spatial prioritisation can support strategic implementation of aquaculture to balance ecosystem-based aquaculture development with environmental conservation, offering a replicable framework for other regions facing similar challenges. This approach provides a pathway for achieving long-term sustainability in aquaculture, contributing to global food security and ecological resilience.

Conservation for production? The benefits of mangroves for sustainable shrimp aquaculture - Aji W. Anggoro; Miguel Castro; Muhammad Ilman; Sara Leavitt; Basir; Mariski Nirwan; Vabian Adriano; Andi Trisnawati; Topik Hidayat; Rahmadi Muis; Dzimar A. R. Prakoso; Yusuf Fajariyanto; et al. (Aquaculture International, 2025)

Wild spices and their ecosystem service contributions in smallholder agroforestry systems of Aceh, Indonesia - Muhammad Jamil; Adnan Adnan; Heri Irawan; Zidni Ilman Navia; Adi Bejo Suwardi (Agroforestry Systems, 2025)

Soil remediation and nano-biosilica: a potential combination to improve the environmental quality of brackishwater aquaculture ponds affected by acid sulfate soils - Tarunamulia Tarunamulia; Akhmad Mustafa; Mudian Paena; Akmal Akmal; Mohammad Syachuddin; Kamariah Kamariah; Erna Ratnawati; Muhammad Ilman (Environmental Science and Pollution Research, 2024)

Microplastics leaving a trace in mangrove sediments ever since they were first manufactured: A study from Indonesia mangroves - Muhammad Reza Cordova; Yaya Ihya Ulumuddin; Ali Arman Lubis; Muhammad Taufik Kaisupy; Singgih Prasetyo Adi Wibowo; Riyana Subandi; Deny Yogaswara; Triyoni Purbonegoro; Jeverson Renyaan; Doni Nurdiansah; Untung Sugiharto; Dienda Shintianata; et al. (Marine Pollution Bulletin, 2023)

Contributions of mangrove conservation and restoration to climate change mitigation in Indonesia - Virni Budi Arifanti; John Boone Kauffman; Subarno; Muhammad Ilman; Anna Tosiani; Nisa Novita (Global Change Biology, 2022)
Mangrove forests are important carbon sinks, and this is especially true for Indonesia where about 24% of the world's mangroves exist. Unfortunately, vast expanses of these mangroves have been deforested, degraded or converted to other uses resulting in significant greenhouse gas emissions. The objective of this study was to quantify the climate change mitigation potential of mangrove conservation and restoration in Indonesia. We calculated the emission factors from the dominant land uses in mangroves, determined mangrove deforestation rates and quantified the total emissions and the potential emission reductions that could be achieved from mangrove conservation and restoration. Based on our analysis of the carbon stocks and emissions from land use in mangroves we found: (1) Indonesia's mangrove ecosystem carbon stocks are among the highest of any tropical forest type; (2) mangrove deforestation results in greenhouse gas emissions that far exceed that of upland tropical deforestation; (3) in the last decade the rates of deforestation in Indonesian mangroves have remained high; and (4) conservation and restoration of mangroves promise to sequester significant quantities of carbon. While mangroves comprise only ≈2.6% of Indonesia's total forest area, their degradation and deforestation accounted for ≈10% of total greenhouse gas emissions arising from the forestry sector. The large source of greenhouse gas emissions from a relatively small proportion of the forest area underscores the value for inclusion of mangroves as a natural climate solution. Mangrove conservation is far more effective than mangrove restoration in carbon emissions reductions and an efficient pathway to achieve Indonesia's nationally determined contribution (NDC) targets. The potential emission reduction from halting deforestation of primary and secondary mangroves coupled with restoration activities could result in an emission reduction equivalent to 8% of Indonesia's 2030 NDC emission reduction targets from the forestry sector.